2015
DOI: 10.1177/1077546315598032
|View full text |Cite
|
Sign up to set email alerts
|

Studies of band gaps in flexural vibrations of a locally resonant beam with novel multi-oscillator configuration

Abstract: To realize a broadened band gap as a potential application of vibration control in the electric vehicle powertrain system requires, a novel configuration of locally resonant (LR) beam with multi-oscillators attached is proposed, in which two types of oscillators are periodically and alternately attached at identical intervals. An analytical model is proposed based on transfer matrix method, which is validated by a finite element simulation. The band gaps in flexural vibration generated by this novel structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Substituting Eqs. (15) into the differential df f0 = dX 2 √X obtained from the definition X = ω 2 /ω 2 0 easily leads to . The roots provides the eigen frequencies and so the band gap limits for C = 0 (full line), C = 0.6 (dashed line), C = 0.9 (dotted line).…”
Section: Dispersion Curves and Analytical Derivation Of The First Banmentioning
confidence: 99%
See 1 more Smart Citation
“…Substituting Eqs. (15) into the differential df f0 = dX 2 √X obtained from the definition X = ω 2 /ω 2 0 easily leads to . The roots provides the eigen frequencies and so the band gap limits for C = 0 (full line), C = 0.6 (dashed line), C = 0.9 (dotted line).…”
Section: Dispersion Curves and Analytical Derivation Of The First Banmentioning
confidence: 99%
“…The insertion of local resonances also leads to many architected layouts leading to structures that efficiently open band gaps [9,10,11,12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical results were validated by experimentally measured FRF on a finite periodic beam specimen, with special attention on the material damping in the rubber. Zuo et al [66] investigated the band gaps by TMM with the results validated by FEM, and observed the effects of band-gap coupling, the intervals, and oscillator parameters. In the case of attached resonators with more finite DOF, Xiao et al [67] extended the PWE method to study the complex band structures of locally resonant beams attached with multiple periodic arrays of spring-mass resonators based on EBT, which were validated by the FRF obtained with commercial FEM software.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been developed for band structure calculation. Transfer Matrix (TM) method is widely used 5,[13][14][15][16][17][18] in 1D periodic beams and multi-layered structure. However, the TM method usually can only be applied in one direction.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, as the main medium for 1D propagation with attached resonators, Timoshenko beam theory has been used by Yu et al 13,26 to study the band structures of metamaterial beams with the transfer matrix method. Extensive studies 14,16,21,27,28 have been done on locally resonant structures based on Euler-Bernoulli and Timoshenko beam theories.…”
Section: Introductionmentioning
confidence: 99%